2022
DOI: 10.31534/engmod.2022.1.ri.02m
|View full text |Cite
|
Sign up to set email alerts
|

Box-Girder Bridges - Modelling and Analysis

Abstract: The box-girder bridge has become very popular lately due to its serviceability, stability, and structural efficiency. The study of such a bridge requires analytical, experimental, or numerical methods. The structural behavior of the box-girder bridge is very complex and is quite cumbersome to be investigated by conventional methods. This paper presents a modelling process for the analysis of simply supported reinforced concrete (RC) box-girder bridges (straight, skew, curve, and skew-curved) using the finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Numerical analyses include modal analysis; static analysis under gravity load, prestressing load lane live load; and whole-process analysis taking into account the building technique and long-term behavior of concrete. Preeti et al (2022) showed the design forces of simply supported single-cell reinforced concrete (RC) curved box-girder bridges using CSiBridge v.20 software based on the finite element method (FEM). N on-dimensional equations are made for figuring out forces and deviations so that results for straight bridges can be used to figure out the same things for curved bridges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical analyses include modal analysis; static analysis under gravity load, prestressing load lane live load; and whole-process analysis taking into account the building technique and long-term behavior of concrete. Preeti et al (2022) showed the design forces of simply supported single-cell reinforced concrete (RC) curved box-girder bridges using CSiBridge v.20 software based on the finite element method (FEM). N on-dimensional equations are made for figuring out forces and deviations so that results for straight bridges can be used to figure out the same things for curved bridges.…”
mentioning
confidence: 99%
“…Also, the analysis indicated that the reduction in bearing load capacity with increasing beam curvature is the same no matter what the b/d ratio is. Preeti et al (2022) used CSiBridge software to simulate and analyze a single-cell and double-cell rectangle-shaped box-girder bridge under the influence of varied IRC loadings. Stress and deflection limits were examined for various span-depth ratios.…”
mentioning
confidence: 99%